2021
DOI: 10.1186/s13047-020-00444-6
|View full text |Cite
|
Sign up to set email alerts
|

Technology‐enabled remote management of diabetes foot disease and potential for reduction in associated health costs: a pilot study

Abstract: Diabetes-related foot disease, particularly when associated with amputation, affects quality of life and has a significant impact on health care costs. A pilot study using enhanced technology to facilitate remote access and video conferencing from rural locations to the diabetes MDT through a new service pathway confirmed high levels of patient satisfaction with 89% of foot ulcers improved or stable and only two minor amputations. A health economic analysis suggested potential for significant cost savings if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Primary users in our study reported high rates of satisfaction with the Healthy.io Minuteful for Wound Digital Management System. Patients are generally in favor of remote wound monitoring based on data from prior studies, including studies specific to DFU ( 29 31 ). In a scoping review of telemedicine solutions for DFU, four main maps emerged: “A whole human not merely a hole in a human,” “Less of a burden on the family, the community, and the environment,” “Competences and continuity of care are essential for high-quality care” and “The quality and modality of the technology.” Consistent with these concepts, our patients reported less frequent in-person appointments, better continuity of care, and more accountability with care as benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Primary users in our study reported high rates of satisfaction with the Healthy.io Minuteful for Wound Digital Management System. Patients are generally in favor of remote wound monitoring based on data from prior studies, including studies specific to DFU ( 29 31 ). In a scoping review of telemedicine solutions for DFU, four main maps emerged: “A whole human not merely a hole in a human,” “Less of a burden on the family, the community, and the environment,” “Competences and continuity of care are essential for high-quality care” and “The quality and modality of the technology.” Consistent with these concepts, our patients reported less frequent in-person appointments, better continuity of care, and more accountability with care as benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Main et al. ( 31 ) piloted another tablet-based application combining wound photo imaging and remote telemedical video conferencing consultations on the NHSNearMe platform with 31 DFU patients. The authors report an 89% rate of healed, improved, or stable ulcers with improved healing in 49.1% (out of 55 ulcers).…”
Section: Resultsmentioning
confidence: 99%
“…No studies attempt to combine more than three DHTs and thus to combine multiple data sources for diagnosis or personalised intervention. Only four of 81 studies combined objective (from sensors and images) and subjective (via mobile phone apps) data ( 30 , 31 , 35 , 36 ).…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
“…Digital technology is important in supporting health services, including improving nursing care, education, and decision making. [1][2][3][4][5][6] Digitalization provides convenience and has a positive impact on the health sector, 1 which is currently experiencing demand for a fast and precise shift. The coronavirus disease 2019 (COVID-19) pandemic has also encouraged the acceleration of the use of digitalization in health services for reasons of physical restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has also encouraged the acceleration of the use of digitalization in health services for reasons of physical restrictions. 1,7,8 The use of digital technology in this era aims to reduce the speed of transmission of contact transmission of infection. 8,9 Some of the developments in digitalization in the COVID-19 era include telemedicine and telenursing.…”
Section: Introductionmentioning
confidence: 99%